Ciclo de vida e dinâmica populacional de espécies nativas de Copepoda Cyclopoida em cultivos de laboratório - Duarte, Matheus Almeida (Universidade Federal de São Carlos, 2017)
The present knowledge on the distribution and diversity of small cyclopoid copepods is rather incomplete, especially in tropical regions. Also scarce is information regarding the individual development and population growth for most species already described. Taking into account the environmental changes caused by anthropogenic activities in natural environments, and in particular the accelerated degradation of aquatic ecosystems besides climatic global changes, one of the main concerns is the possibility that many species can be extinct even before being known by mankind. Considering this scenario and because some species at risk are endemic to the Neotropical region, the present study aimed to gather information regarding the life cycle and population dynamics of three small freshwater cyclopoids: Ectocyclops herbsti, Eucyclops ensifer and Microcyclops anceps whose life cycles were not studied before. Sampling of specimens were respectively carried out at three different localities: Mayaca Lake (São Carlos, SP), Corrego da Igualdade (São Manoel, SP) and a pond in Miranda River floodplain, Pantanal matogrossense (Corumba, MS). Ovigerous females of each species were sorted out and maintained in the laboratory at constant and controlled conditions: 25 °C temperature, 12/12 h photoperiod in a growth chamber until the egg eclosion. Newly born nauplii were used for life cycle experiments under the same controlled conditions just described and daily fed with algal suspension of Pseudokirchneriella subcapitata at approximately 105 cells mL-1, in order to assess the main parameters of the three copepods life cycle and population dynamics. Mean embryonic development duration for Ectocyclops herbsti was 1.81 ± 0.53 days and 18 ± 0.7 days for the post embryonic development. Mean longevity of E. herbsti under the culture conditions was 50.43 ± 20.73 days. Eucylops ensifer had mean duration of embryonic development of 1.03±0.24 days, post-embryonic duration of 13.5±2.5 days and mean longevity of 48.5 ± 26.5 days. For Microcyclops anceps the mean embryonic and post-embryonic development times were 1.07 ± 0.12 and12 ± 2.5 days, respectively. The mean longevity of M. anceps was 30 ± 15 days. The survival curves of species laboratory first generations followed the concave type with great mortality in the beginning of life, relatively stable mortality rates after surpassing the critical transition of last nauplii instar into first copepodid stage, but with higher mortality rates close to the end of life. Comparisons of life cycle parameters from these species and also among these and other copepods show that the species studied have short generation times and high individual growth rates, thus suggesting they could play relevant roles in the community and in the functioning of the ecosystem they inhabit.
Keywords: Ciclos de vida; Espécies nativas; Distribuição geográfica; Copepoda Cyclopoida; CIENCIAS BIOLOGICAS::ECOLOGIA